Paleowind directions from the magnetic fabric of loess deposits in the western Chinese Loess Plateau and implications for dust provenance. (September 2021) - Gao, Xinbo; Hao, Qingzhen; Ge, Junyi; Han, Long; Fu, Yu; Wu, Xuechao; Deng, Chenglong; Marković, Slobodan B.; Guo, Zhengtang
Abstract: The aeolian loess-paleosol sequences in the Chinese Loess Plateau (CLP) are an excellent archive of variations in atmospheric circulation in the geological past. However, there is no consensus regarding the roles of the East Asian winter monsoon and westerly winds in transporting the dust responsible for loess deposition during glacial and interstadial periods. We conducted detailed measurements of the anisotropy of magnetic susceptibility (AMS) on two parallel loess profiles covering the most recent 130 ka in the western CLP to determine paleowind directions. Results show that the magnetic lineations of the loess and paleosol units in both sections are significantly clustered along the northwest to southeast direction. These observations demonstrate that the prevailing wind system responsible for dust transport in the western CLP was the northwesterly winter monsoon, rather than the westerly winds. The AMS-derived dust-bearing wind direction was relatively stable during the last glacial and interglacial cycle in the western CLP, consistent with sedimentary and AMS evidence from the eastern CLP. Accordingly, it is reasonable to conclude that large areas of deserts and Gobi deserts areas located in the upwind direction were the dominant sources for the aeolian deposits of the Loess Plateau.